Latihan Aerobik Jalan Kaki pada Pasien Diabetes Mellitus Tipe II - I Dewa Putu Gede Putra Yasa; VM Endang SP Rahayu (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2014)
The purpose of this study is to determine effect of walking aerobik exercise of capillary refill time of the lower extremities of diabetic type II patients. This study used quasy experiment design with non-equivalent group design performed on 30 samples. The samples was taken by purposive sampling. The data was collectted by physical examination capillary refill time (CRT) using stopwatch.The results showed an average CRT lower extremities before doing walking aerobik exercise in the treatment group is 2,87 seconds and 2,72 seconds for control groups. After given walking aerobik exercise obtained an average CRT lower extremities in the treatment group is 1,48 seconds and 2,77 seconds for control group. The results of data analysis with independent ttest there was a significant effect of walking aerobik exercise with CRT from the lower extremities in patients with diabetes mellitus type II, p = 0.001 (α = 0.05)